PENGARUH SOSIALISASI PAJAK, PEMERIKSAAN PAJAK DAN SUNSET POLICY JILID II TERHADAP PENERIMAAN PAJAK PENGHASILAN BADAN DI KPP MADYA PEKANBARU - Rahman, Opnita; Ritonga, Kirmizi; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to find out whether tax socialization, tax inspection and sunset policy have a significant influence to income tax receivable in Madya Pekanbaru Tax Authority. The population in this study are all registered tax prayer in Madya Pekanbaru Tax Authority.The Number of samples in this study were 155 respondents in Pekanbaru area. Samples were selected by using purposive sampling which the criteria. Data collection was conducted by distributing 206 questinary, however only 155 questionnaires were replied by using purposive sampling method. The analytical tool used in this study was Statistical Package for the Social (SPSS). Tax socialization positive and significant impact on income tax receivable. T test 8,283 with a significance value < 0,05 so H1 accepted. Tax inspection positive and significant impact on income tax recevaible. T test 2,521 with a significance value < 0,05 so H2 accepted. Sunset policy positive and significant impact on income tax receivable. T test 3,425 wit a significance value < 0,05 so H3 accepted. Based on the result of data analysis known that the tax socialization, tax inspection and sunset policy affect significantly positive on the income tax receivable.Variable tax socialization, tax inspection and sunset policy can be used to explain to the income tax receivable of 54,7%Keyword: socialization, inspection, policy, income tax